2013
DOI: 10.1002/ejic.201201437
|View full text |Cite
|
Sign up to set email alerts
|

Nanoaggregates of Simple Mn Porphyrin Complexes as Catalysts for the Selective Oxidation of Hydrocarbons

Abstract: A stable suspension of simple manganese(III) meso‐tetraphenylporphyrin nanoaggregates was prepared by a host–guest procedure, in which ethanol and water are used as “green” solvents. The organic nanoparticles were studied by dynamic light scattering (DLS), AFM, and UV/Vis and fluorescence spectroscopy. The results indicate that the nanoaggregates have a spherical morphology with sizes between 15–40 nm. The epoxidation of olefins and oxygenation of saturated hydrocarbons by PhI(OAc)2 were efficiently enhanced w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 68 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…However, high aggregation tendency of free Mn(TPP)OAc catalyst in aqueous media should be taken into account for such an deciency. 22,24 The systematic investigations of reaction temperature and oxidant amounts demonstrated that aqueous mixture of Fig. 2 TEM images of 6.0 (A) and 120 mg (B) of Mn(TPP)OAc@SMNP in water.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, high aggregation tendency of free Mn(TPP)OAc catalyst in aqueous media should be taken into account for such an deciency. 22,24 The systematic investigations of reaction temperature and oxidant amounts demonstrated that aqueous mixture of Fig. 2 TEM images of 6.0 (A) and 120 mg (B) of Mn(TPP)OAc@SMNP in water.…”
Section: Resultsmentioning
confidence: 99%
“…Regardingly, magnetic nanoparticles are one of the most widely studied materials in multi-disciplinary research including biotechnology, biomedicine, magnetic resonance imaging (MRI), separation and catalysis. [11][12][13][14][15] In continuation of our research on the development of greener oxidation protocols and nanocatalysis, [18][19][20][21][22][23][24][25][26][27] herein, we would like to describe a new environmentally benign method for economic production of epoxides, carbonyl compounds and sulfoxides, all of which are invaluable precursors in industry as well as pharmaceutical synthetic chemistry. 1 The reactions proceed in water using tert-butyl hydroperoxide (TBHP, 70%) under catalytic inuence of new synthesized Mn(TPP) OAc@SMNP as a magnetically recoverable porphyrin nanocatalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we wish to use pyridine‐functionalized γ‐Fe 2 O 3 nanoparticles as a competent support for coordinative anchoring of simple cobalt(II) salophen complex as a heterogeneous catalyst for selective oxidation of benzyl alcohols. The pyridine attached to MNP could improve the catalytic efficiency and stability of salophen complex . The catalyst could be easily and efficiently separated from the reaction mixture by the application of an external magnetic field and proved to be reusable.…”
Section: Introductionmentioning
confidence: 92%
“…The pyridine attached to MNP could improve the catalytic efficiency and stability of salophen complex. [16][17][18] The catalyst could be easily and efficiently separated from the reaction mixture by the application of an external magnetic field and proved to be reusable.…”
Section: Introductionmentioning
confidence: 99%
“…8 In analogy to inorganic and other organic nanoparticles, it is predictable that nanoparticles of porphyrins will have unique photonic properties not accessible by larger-scaled materials having the macrocycle, or by the molecules themselves. 9,10 The promising results obtained in our recent work on the synthesis and catalytic oxidation activity of Mn-porphyrin nanoparticles 11 induced us to investigate a computational density functional theory (DFT) study to describe the effect of diverse agents on the structure and activity of manganese(V)-oxo meso-tetraphenylporphyrin. [12][13][14] Herein, new porphyrinic dimers comprising two distinct oxo-Mn-porphyrin complexes containing nitrogen donors is designed which are linked to each other through phenyl/phenyl as well as axial ligands interactions.…”
Section: Introductionmentioning
confidence: 99%